Analysis of Well Water Quality and its Relationship with the Incidence of Diarrhea in Children in South Coastal Area: A Cross sectional Study - Lieza Corsita; Jernita Sinaga (Miracle Journal Get Press, 2025)
Diarrhea remains a leading cause of morbidity and mortality among children under five, especially in developing countries like Indonesia. Contaminated water that fails to meet physical and microbiological standards significantly contributes to disease transmission in children. This study employed a quantitative, observational analytic cross-sectional design to examine the relationship between well water quality and childhood diarrhea incidence in southern coastal areas. A total of 100 households with children aged 1-5 years, relying on well water for drinking, participated. Univariate analysis described respondent characteristics and water quality, while chi-square tests assessed associations between well water quality and childhood diarrhea incidence. Bivariate and multivariate logistic regression analyses determined risk magnitudes (odds ratios). The findings indicated a significant association between microbiological contamination of household well water and diarrhea occurrence in children (p = 0.001; OR = 4.00). Additionally, wells located less than 10 meters from septic tanks posed a higher risk (OR = 2.67). Although differences in well type (dug vs. drilled) were observed, they were not statistically significant (p = 0.202). These results indicate that poor well water quality is a major risk factor for diarrhoea in children in the southern coastal region. To reduce this risk, public health efforts need to focus on improving access to clean water, environmental sanitation education, and technical supervision in the construction and maintenance of wells. This integrated approach is important for reducing the incidence of diarrhoea in children and improving the health status of children in affected communities.